2003
DOI: 10.33584/jnzg.2003.65.2499
|View full text |Cite
|
Sign up to set email alerts
|

The effect of grass-endophyte associations on feeding of Canada geese (Branta canadensis)

Abstract: Canada geese (Branta canadensis) and other herbivorous birds (e.g. paradise ducks, pukeko) can be a significant problem for both pastoral farmers and recreational turf managers in a number of locations in New Zealand. Canada geese were offered seeds and herbage of selected ryegrass combinations of (Lolium perenne) and endophyte (Neotyphodium lolii) to examine the effects of endophyte and the associated alkaloids on feeding behaviour. Forty geese were captured annually during the moult in January and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Establishing endophytic tall fescue at airports has potential for deterring geese whose resident populations may relocate to areas with better forage (Conover, 1991; Coley et al, 1995; Pennell and Rolston, 2003; Washburn et al, 2007). This study focused on another proposed mechanism (e.g., Pennell et al, 2015) by which E+ grasses might indirectly reduce strike hazard by suppressing the types of invertebrates that attract insectivorous birds.…”
Section: Discussion and Applicationsmentioning
confidence: 99%
“…Establishing endophytic tall fescue at airports has potential for deterring geese whose resident populations may relocate to areas with better forage (Conover, 1991; Coley et al, 1995; Pennell and Rolston, 2003; Washburn et al, 2007). This study focused on another proposed mechanism (e.g., Pennell et al, 2015) by which E+ grasses might indirectly reduce strike hazard by suppressing the types of invertebrates that attract insectivorous birds.…”
Section: Discussion and Applicationsmentioning
confidence: 99%
“…in appearance, smell and texture) then repeated exposure to that newly-modified source is generally required in order to alter the learned behavior. This response has been reported for Canada geese (Pennell & Rolston 2003;Pennell et al 2010) feeding on certain Epichloë-endophyteinfected grasses, with the behavior termed postingestion feedback (Conover & Messmer 1996b). This response, from Avanex grasses, has also been evaluated on small mammalian species including mice (Mus musculus) and rabbits (Oryctolagus cuniculus) (Finch et al 2016;Pennell et al 2017a).…”
mentioning
confidence: 85%
“…Ergovaline has a deterrent effect on grazing animals (Pennell and Rolston 2003). This has been demonstrated in cattle where a study showed animals grazing endophyte-infected tall fescue had lower feed intakes than animals grazing endophyte-free tall fescue (Stuedemann et al 1989;Seman et al 1990).…”
Section: Feed Deterrent Effectmentioning
confidence: 99%